2015
DOI: 10.1530/eje-14-0654
|View full text |Cite
|
Sign up to set email alerts
|

GH deficiency after traumatic brain injury: improvement in quality of life with GH therapy: analysis of the KIMS database

Abstract: Objective: Prevalence of GH deficiency (GHD) caused by traumatic brain injury (TBI) is highly variable. Short-term studies show improvement in quality of life (QoL) during GH replacement (GHR), but long-term data are lacking. The aim of this study was to analyse the clinical characteristics of post-traumatic hypopituitarism and the QoL effects of long-term GHR. Design/methods: Pfizer International Metabolic Database patients with GHD caused by TBI and by non-functioning pituitary adenoma (NFPA) were compared r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…In a third study [18], the Pfizer International Metabolic Database was retrospectively reviewed, and patients with GH deficiency caused by TBI ( n = 564) and non-functioning pituitary adenoma ( n = 3773) were compared with regard to clinical characteristics at baseline and after 1 year of GH replacement therapy. QoL was examined after up to 8 years.…”
Section: Pharmacological Agents With Demonstrated Neuroprotective Ementioning
confidence: 99%
“…In a third study [18], the Pfizer International Metabolic Database was retrospectively reviewed, and patients with GH deficiency caused by TBI ( n = 564) and non-functioning pituitary adenoma ( n = 3773) were compared with regard to clinical characteristics at baseline and after 1 year of GH replacement therapy. QoL was examined after up to 8 years.…”
Section: Pharmacological Agents With Demonstrated Neuroprotective Ementioning
confidence: 99%
“…In recent years, there has been an increasing amount of strong evidence that suggests that patients with TBI are at considerable risk of dysfunction of the hypothalamic-pituitary axis, and this risk is associated with morbidity and possibly mortality 69 . Furthermore, clinical trials have demonstrated that treatment with replacement hormones is convenient and physiologically relevant 9, 10 . According to one report, the incidence of hypothalamic-pituitary dysfunction induced by TBI is 5.4% to 90% 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although many clinical trials have focused on dysfunction of the hypothalamic-pituitary axis caused by TBI 10, 1921 , few studies have paid close attention to neuroendocrine and physiopathological alterations of the hypothalamic-pituitary axis induced by TBI in the acute phase. It is interesting to explore the neuroendocrine changes and apoptosis of brain cells in the hypothalamic-pituitary axis that are caused by intracranial hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…35 Initial screening for GH (and ACTH) deficiency was performed using the glucagon stimulation test with peak GH cutoff <5lg/l. 35 The diagnosis of GHD was then confirmed using the GHRH-arginine test, with age-and BMI-adjusted cutoffs, 21 and/or insulin tolerance test (peak GH <3lg/l), in all patients. Serum GH was assayed using the Immulite 2000 assay.…”
Section: Endocrine Assessmentmentioning
confidence: 99%
“…29,32,33 Following TBI, GH replacement also improves cognition, psychological function, and quality of life (QoL) in patients with GHD. [34][35][36][37][38] This could be produced through an effect on WM tract recovery, and changes in the levels of IGF-I might mediate this effect. However, the effects of GHD/IGF-I status on WM recovery following TBI are unknown.…”
mentioning
confidence: 99%